1996
DOI: 10.1097/00005176-199607000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Four Hour Ambulatory Gastric and Duodenal pH Profiles in Cystic Fibrosis: Effect of Duodenal Hyperacidity on Pancreatic EnzymeFunction and Fat Absorption

Abstract: Overt steatorrhoea remains a problem for some patients with cystic fibrosis (CF) despite supraphysiological dosages of pancreatic enzymes. As pancreatin release and enzyme function is influenced by duodenal pH, we have used 24-h ambulatory pH measurements to assess the extent and duration of postprandial hyperacidity. Readings were obtained from the stomach and proximal duodenum in 16 CF patients (aged 6 months to 12 years) using a dual-channel antimony electrode. The fasting gastric and duodenal pH values wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
41
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 13 publications
4
41
0
2
Order By: Relevance
“…Bicarbonate-rich fluid secretion is necessary for neutralization of acid entering the duodenum from the stomach. It was shown previously that the duodenal pH in the CF mouse is abnormally acidic due to lack of CFTR (9), which is similar to human CF patients (1).…”
supporting
confidence: 56%
“…Bicarbonate-rich fluid secretion is necessary for neutralization of acid entering the duodenum from the stomach. It was shown previously that the duodenal pH in the CF mouse is abnormally acidic due to lack of CFTR (9), which is similar to human CF patients (1).…”
supporting
confidence: 56%
“…Enhanced gastric acid secretion in patients with CF has been previously observed (49)(50)(51); however, these findings differ from studies in DF508-CFTR mice that exhibit reduced gastric acid secretion in comparison to control mice (52). Duodenal pH in humans with CF (45,53) and CFTR-KO mice (46,47) has also been shown to be lower than in non-CF controls. Although our studies demonstrated no differences in gastrointestinal pH in newborn CF ferrets, we cannot conclude that alterations in pH may occur with increased age and/or after feeding.…”
mentioning
confidence: 64%
“…With respect to the luminal pH of small intestine, almost identical patterns were observed between children aged 8-14 years and adults, of which the pH gradually increases along the entire small intestine from 6.4 to 7.4 (14). Another study reported the similar duodenal pH between children aged 0.5-12 years and adults (15). Limited information pertaining to the luminal pH of small intestine was reported for neonates by Barbero et al (16), through our comprehensive literature searches in MEDLINE and EMBASE databases (from inception to June, 2014).…”
mentioning
confidence: 78%